Acute Antibody-mediated Rejection Coexisting With T Cell–mediated Rejection in Pediatric ABO-incompatible Transplantation. Issue 9 (4th August 2022) - Yanagi, Yusuke; Sakamoto, Seisuke; Yamada, Masaki; Mimori, Koutaro; Nakao, Toshimasa; Kodama, Tasuku; Uchida, Hajime; Shimizu, Seiichi; Fukuda, Akinari; Nakano, Noriyuki; Haga, Chiduko; Yoshioka, Takako; et al.
Abstract : Background: The management and outcome of ABO-incompatible (ABO-I) liver transplantation (LT) has been improving over the past few decades. Recently, the introduction of a pathological evaluation of acute antibody-mediated rejection (AMR) for liver allograft has provided a new recognition of allograft rejection in LT. Methods: One hundred and one pediatric ABO-I LTs performed in our institute were retrospectively analyzed. We assessed the clinical manifestations, diagnosis, and treatment of acute AMR, focusing on the recipient age and pathological findings. Results: Twelve cases (11.9%) of acute AMR related to ABO-I were observed. Nine cases developed mixed T cell–mediated rejection (TCMR)/AMR. These consisted of 6 patients in the younger age group for whom the preconditioning treatment was not indicated and 4 patients in the older age group to whom rituximab was administered as planned. Two patients in the older age group to whom preoperative rituximab was not administered as planned developed isolated AMR. Acute AMR in the older group required plasma exchange for treatment, regardless of the coexistence of TCMR. In contrast, those in the younger group were successfully treated by intravenous methylprednisolone pulse and intravenous immunoglobulin without plasma exchange, accounting for mild immune reaction. Conclusions: Acute ABO-I AMR can develop simultaneously with TCMR, even in young patients with a compromised humoral immune response following ABO-I LT. Establishing the accurate diagnosis of AMR with a pathological examination, including component 4d staining, is crucial for optimizing treatment.